(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The aim of this paper is to investigate whether the right to know one’s genetic origins (RKGO) encounters significant differences in the level of guarantee when it applies to adoption, to assisted reproduction or to surrogacy. The results of this analysis are aimed at understanding the degree of effectiveness of this right in different legal systems. To this end, the main features of the right to know one’s genetic origins are carefully considered, the research being based both on legislative and on jurisdictional materials. Namely, the essay focuses on information and consent, on the structure of relevant regulation in the balance between collection and storage of personal information or protection of anonymity and privacy and, finally, on the most crucial factor for the enforcement of this right, namely time.